2006
DOI: 10.1111/j.1748-720x.2006.00015.x
|View full text |Cite
|
Sign up to set email alerts
|

Currents in Contemporary Ethics: Shocking Treatment: The Use of Tasers in Psychiatric Care

Abstract: The use of restraints on psychiatric patients has long been criticized, and the need for self-restraint of professionals in response to new technologies has been documented from the nineteenth century. Since the middle ages, when leprosy disappeared from civilized society, individuals with a “deranged mind” came to occupy the public space of outcast once reserved for the leper. This diminished social status conflicts with the ethical precept of respect for all patients and the need for humane treatment within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Secondly, others have demonstrated that it is possible to reduce restraint use and to do so without an attendant increase in staff injury or cost (Andrews, 1978;Taxis, 2002;Smith et al 2005;LeBel & Goldstein, 2005). They can be imposed (Andrews, 1978;Busch & Shore, 2000;Erwin & Philibert, 2006) or internally led endeavours. They can be imposed (Andrews, 1978;Busch & Shore, 2000;Erwin & Philibert, 2006) or internally led endeavours.…”
Section: Conducted Energy Devices (Ceds)mentioning
confidence: 99%
“…Secondly, others have demonstrated that it is possible to reduce restraint use and to do so without an attendant increase in staff injury or cost (Andrews, 1978;Taxis, 2002;Smith et al 2005;LeBel & Goldstein, 2005). They can be imposed (Andrews, 1978;Busch & Shore, 2000;Erwin & Philibert, 2006) or internally led endeavours. They can be imposed (Andrews, 1978;Busch & Shore, 2000;Erwin & Philibert, 2006) or internally led endeavours.…”
Section: Conducted Energy Devices (Ceds)mentioning
confidence: 99%